Education through Athletics: Interest in an Athletics Performance Curriculum - Harry Molly; Erianne A. Weight (Journal of Applied Sports Management, 2019)
Intellectual and life-skill benefits of collegiate athletics participation have been doc-umented in empirical research, yet athletics-centric curricula are traditionally not offered for academic credit in higher education. This pilot study employed a survey, distributed to FBS Division I college varsity athletes, coaches, athletics administra-tors, and faculty from three Atlantic Coast Conference institutions, to explore the interest in an athletics performance minor through the lens of the Integrated View of intercollegiate athletics. The results demonstrate a moderate interest in an ath-letics performance curriculum, with 66% of those surveyed voicing support. Those most supportive were varsity athletes and coaches, while faculty were the least sup-portive. This study adds to the literature by addressing the philosophical dichotomy that despite the nexus between educational outcomes and athletics, an opportunity for academic credit is lacking.
Keywords: Intercollegiate Athletics; Experiential Education; College Sport; Higher Education; Sport for Development: Curriculum